Public Information Disclosure: Mapping the Understanding of Multiple Actors in Corruption- Prone Indonesian Provinces - Lina Miftahul Jannah; Muhammad Yasin Sipahutar; Desy Hariyati (Indonesian Association for Public Administration, 2020)
Recent scholarships in public administration and legal studies have agreed on the role of public information disclosure as a necessary requirement in eradicating corruption. Moreover, it is evident that accessibility of public information to the citizen helps to improve governance reform and policy making. In that situation, the citizen is involved in the participatory process and subsequently tightens public oversight to the government. Nevertheless, the literature might only be valid in relatively homogenous societies or in countries successfully achieving their development goals. This article seeks to confront this scholarship to the prevalence of a country experiencing ongoing construction of administrative law framework amidst discrepancies of development progress across regions. Three provinces in Indonesia are chosen to explain this matter by identifying relevant actors and mapping their understanding about public information disclosure against corruption. We employ qualitative research by process-tracing methods to identify causal mechanisms over multiple determining factors affecting the understanding. Data is inquired through in-depth interviews and analyses of open, accessible electronic data. Our recent work progress suggests that impediments to undertake public information disclosure against corruption come from very basic situations, including a sort of misunderstanding of predefined terminology between disclosed or classified information to the public and over-reliance on prevailing laws related to the issue without any improvements of the regulatory framework or policy instruments.